Analysis of statistical power reconciles drought-conflict results in Africa - Hsiang, Solomon; Burke, Marshall; Miguel, Edward; Meng, Kyle C.; Cane, Mark A. (2015)
Author(s): Hsiang, Solomon M.; Burke, Marshall; Miguel, Edward; Meng, Kyle C.; Cane, Mark A.
openalex: W2777510260 mag: 2777510260
Keywords: openalex:import

Analysis of statistical power reconciles drought-conflict results in Africa - eScholarship - Hsiang, Solomon; Burke, Marshall; Miguel, Edward; Meng, Kyle C.; Cane, Mark A. (2015)
openalex: W2765219511 mag: 2765219511
Keywords: openalex:import